Outcome after laparoscopic versus open wedge resection for suspected gastric gastrointestinal stromal tumors: A matched-pair case–control study. Issue 7 (July 2015) - Goh, B.K.P.; Goh, Y.-C.; Eng, A.K.H.; Chan, W.-H.; Chow, P.K.H.; Chung, Y.-F.A.; Ong, H.-S.; Wong, W.-K.
Abstract Background Laparoscopic resection of gastric gastrointestinal stromal tumors (GISTs) has been shown by several retrospective studies to be technically feasible and associated with favorable outcomes when compared to the open approach. This study aims to mitigate potential selection bias by performing a case control study of laparoscopic (LWR) versus open wedge resection (OWR) matched by resection type, location and tumor size. Methods We retrospectively identified 50 consecutive patients who underwent LWR for a suspected gastric GIST from a prospective database and matched this cohort with 50 patients who underwent OWR. Results There was no statistical difference between the key baseline clinicopathological features of patients' who underwent LWR versus OWR. Patients who underwent LWR had longer operating times [150 (range, 65–270) minutes vs 92.5 (25–200) minutes, P < .001] but decreased median blood loss [0 (0–300) ml vs 0 (0–1200) ml, P = .015], decreased frequency of intraoperative or postoperative blood transfusion [1 (2%) vs 8 (16%), P = .031], decreased median time to liquid diet [2 (0–5) vs 3 (1–7) days, P < .001], decreased median time to solid diet [3 (1–6) vs 5 (2–11) days, P < .001] and decreased postoperative stay [4 (2–10) vs 4.5 (3–17), P < .001] compared to OWR. There was no difference in oncological outcomes such as frequency of close margins (≤1 mm) and recurrence-free survival. Conclusion This matched case–control study provides supporting evidence that LWR results in superior perioperative outcomes compared to OWR without compromising on oncological outcomes.